1997
DOI: 10.1002/(sici)1097-4636(19971215)37:4<539::aid-jbm13>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a subcutaneous silicone rubber implant with shallow surface microgrooves on the surrounding tissues in rabbits

Abstract: It has been suggested that during wound healing microtextured surfaces can alter events at the interface be­ tween implant surface surface and surrounding tissues. To investigate this phenomenon, smooth and microtextured silicone rubber implants were implanted subcutaneously in rabbits for 3, 7, 42, and 84 days. The textured implants pos­ sessed parallel surface microgrooves and ridges with a width of 2.0, 5.0, and 10.0 \x.m. All gi'ooves had a depth of approximately 0.5 jxm. SEM observation showed fibroblasts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 24 publications
2
24
0
Order By: Relevance
“…Picha et al (34) have shown that pillared surface texturing of silicone results in reduced fibrosis and increased vascularization in close proximity to the implant. den Braber et al (35) created microgrooves on silicone rubber implants, thereby increasing the vascularity of the resulting capsules. Karp et al (36) observed the presence of capillaries in capsules that formed around implanted Millipore filters.…”
Section: Discussionmentioning
confidence: 99%
“…Picha et al (34) have shown that pillared surface texturing of silicone results in reduced fibrosis and increased vascularization in close proximity to the implant. den Braber et al (35) created microgrooves on silicone rubber implants, thereby increasing the vascularity of the resulting capsules. Karp et al (36) observed the presence of capillaries in capsules that formed around implanted Millipore filters.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have demonstrated that although different cell types behave differently, texturing has strong orientation effects on the cell functions such as migration, proliferation, differentiation and apoptosis and cytoskeleton elements [61][62][63][64][65][66][67][68][69][70][71][72]. Transmission electron microscopy (TEM) studies have demonstrated that cells penetrate into very shallow (≤1 μm) or wide (≥5 μm) microgrooves, wrapping around flat walls or edges.…”
Section: Texturingmentioning
confidence: 99%
“…Den Braber et al, 82 Walboomers et al, 83 and Walboomers and Jansen 84 evaluated the influence of microgrooves on the formation of fibrous capsules around subcutaneous implants inserted in rabbits, guinea pigs, and goats. The results of these studies suggested that microgrooves were unable to influence the wound healing process.…”
Section: Effects Of Microtextures In Vivomentioning
confidence: 99%